Increasing The Results of Learning Distribution Two Numbers With Class II Sd - Hary Raswel (Postgraduate School, Universitas Negeri Padang, 2019)
ABSTRACT This research is motivated by the fact that in the field there are many learning to divide two-digit numbers with teaching aids, especially by means of repetitive reduction which is converse. Learning is still teacher-centered, so learning becomes boring and consequently student learning outcomes are not yet established with KKM, which is 65. One solution to overcome this problem is by using a props approach. Thus the purpose of this study was to describe the form of planning, implementation in improving the learning outcomes of class II SD Negeri 20 Dadok Tunggul black, Koto Tangah Subdistrict, Padang on the material distribution of two-digit numbers resulting from repeated reduction using props. This research was conducted at SD Negeri 20 Dadok Tunggul Hitam, Koto Tangah District, Padang, with 30 students. This type of research is PTK using qualitative and quantitative. The research plan includes planning, implementation, observation, and reflection. This research was carried out two cycles with the material sharing two numbers by means of props. Keywords: Increased Learning Outcomes Sharing Numbers, Two Numbers With, Teaching Aids in Elementary Class